Physiological and biochemical changes of Picea abies (L.) during acute drought stress and their correlation with susceptibility to Ips typographus (L.) and I. duplicatus (Sahlberg) - Basile, Sara; Stříbrská, Barbora; Kalyniukova, Alina; Hradecký, Jaromír; Synek, Jiří; Gershenzon, Jonathan; Jirošová, Anna (Frontiers in Forests and Global Change, 2024)
Introduction In recent years, Norway spruce (Picea abies L.) forests in Central Europe have faced escalating threats from bark beetles, primarily Ips typographus (L.), and other species, such as I. duplicatus (Sahlberg). Outbreaks are partially attributed to weakened tree defense resulting from drought periods induced by climate change. This study examines Norway spruce’s physiological and metabolic reactions to acute drought stress during the growing season and evaluates its susceptibility to I. typographus and I. duplicatus. Methodology In order to induce drought stress, mature Norway spruces had their roots covered with a roof in April 2021, depriving them of water. Control trees were left with free access to natural rainwater. Over 5 months of the growing season, soil water potential, bark temperature, tree trunk circumference, and sap flow were monitored. Roofed trees and controls were sampled in July, August, and September and analyzed for non-structural carbohydrates and the two classes of defensive compounds, phenolics and terpenes. Furthermore, two different bioassays in tubes and boxes were performed using adult I. typographus and I. duplicatus beetles to assess host choice and acceptance. Results Roofed trees exhibited signs of stress as early as July, resulting in decreased tree trunk and a consequent increase in non-structural carbohydrate content. Defensive metabolites remained largely unaffected except for an increase in diterpenes in September. In bioassays, I. typographus preferred boring into the bark of roofed trees in August in tubes and in September in boxes. This increased tree acceptance correlated with increased levels of soluble carbohydrates in the phloem. I. typographus and I. duplicatus beetles showed higher mobility in boxes in August and September on roofed trees but not in July, even though bark surface temperatures were elevated in roof-covered trees during all three bioassay periods. Conclusion The study revealed rapid physiological responses of trees to acute drought stress, although not many changes were observed in defense traits. Despite the absence of natural bark beetle attacks, drought trees were more accepted by I. typographus than naturally watered trees. This response may indicate the beetles’ preference for trees with phloem of higher nutritional quality induced by the acute drought stress conditions.